Textes savants et pratiques numériques : le projet Poésie biblique latine antique et médiévale (PoBLAM) - Bruno Bureau; Inès Burri (Humanités Numériques)
The aim of this article is to share the reflections arising from some digital components of the ANR‑DFG PoBLAM project. Based on the more general questions raised by the use of digital humanities in this context, we present the impact of the technical aspects of the project on our implementation plans. Although all the projects deal with a common subject, Latin and medieval biblical poetry, we had to adopt very different approaches because of the differences in their nature: they are in fact a hypertext, a scholarly edition and a database. The second part of the article offers a detailed explanation of our technical choices and their justification in the precise context of PoBLAM’s expectations.